Malory Towers Collection 1 - Enid Blyton (London Hodder childrens Books, 2016)
There's more to life than lessons at Malory Towers, Enid Blyton's best-loved boarding school series. This fantastic bumper collection contains Malory Towers books 1-3, with a brand-new cover illustrated by Pippa Curnick. First TermDarrell Rivers is thrilled to start her first term at boarding school. She soon makes friends - and mischief! Another new girl, Gwendoline is beginning to get on everyone's nerves. Will Darrell be able to keep her fiery temper under controlSecond FormDarrell Rivers is excited to be going into her second year at Malory Towers - but is she ready for the drama it will bring Jealousy flares when a new head of the form is chosen, and the girls become suspicious when their belongings go missing. And why on earth has timid Mary-Lou ventured out during a terrible storm Third YearThis term, the girls get a surprise when Darrell Rivers returns to Malory Towers with a glamorous new girl in tow. Zerelda soon catches everyone's eye for all the wrong reasons! Meanwhile, Bill is causing a stir with her horse-mad ways - and there's a big shock in store for Darrell . . . Between 1946 and 1951, Enid Blyton wrote six novels set at Malory Towers. This collection features the original stories and is unillustrated.
Keywords: Mystery -- Mystery